Foreign language writing anxiety among preservice EFL Teachers - Rodríguez, Yarimax; Delgado, Verónica; Colón, José Manuel (Lenguas Modernas, 2017)
In the present study, the existence of foreign language writing anxiety, related to but distinct fiom general foreign language anxicty and native languagc writing anxiety was examincd. A total of 120 English rnajors from two Venezuelan universities participated in the study. Three scales were used to measure the language anxieties under study: The Foreign Language Classroom Anxicty Scale (FLCAS) to measure foreign language anxicty; The Second Language Writing Anxiety Inventory (SLWAI) to assess foreign language writing anxiety; and The Native Language Writing Anxiety Inventory OLWAI) to measure native language writing anxiety. The results provided strong evidence suggesting the existcnce of foreign language writing anxiety. Furthermore, they indicated that while gender had a statistically signiflcant effect on both fbreign language anxicties, institution had a significant eflect on all three language anxieties.